2015
DOI: 10.18632/oncotarget.6312
|View full text |Cite|
|
Sign up to set email alerts
|

Protein 4.1N acts as a potential tumor suppressor linking PP1 to JNK-c-Jun pathway regulation in NSCLC

Abstract: Protein 4.1N is a member of protein 4.1 family and has been recognized as a potential tumor suppressor in solid tumors. Here, we aimed to investigate the role and mechanisms of 4.1N in non-small cell lung cancer (NSCLC). We confirmed that the expression level of 4.1N was inversely correlated with the metastatic properties of NSCLC cell lines and histological grade of clinical NSCLC tissues. Specific knockdown of 4.1N promoted tumor cell proliferation, migration and adhesion in vitro, and tumor growth and metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…It was previously demonstrated that protein 4.1N, a member of the protein 4.1 family, was able to suppress metastasis by inactivating JNK-c-Jun signaling pathway in NSCLC (34). Celastrol induces cisplatin re-sensitization through inhibition of the JNK/activating transcription factor 2 signaling pathway in NSCLC (35).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that protein 4.1N, a member of the protein 4.1 family, was able to suppress metastasis by inactivating JNK-c-Jun signaling pathway in NSCLC (34). Celastrol induces cisplatin re-sensitization through inhibition of the JNK/activating transcription factor 2 signaling pathway in NSCLC (35).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental protocols were conducted according to our published protocol23. Transfected cells were seeded in 6-well cell culture plates and cultured until 90–100% confluent in complete medium.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental protocols were conducted according to our published protocol23. Cells (4 × 10 5  cells/well) were transfected and seeded into the top chamber of 24-well Transwell plates (Corning Incorporated, USA) containing 1% FBS medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations